1992
DOI: 10.3109/00048679209072062
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachments and Sexuality: Implications for Understanding Risk Behaviours for HIV Infection

Abstract: In response to the AIDS epidemic, there has been an intensification of interest in human sexuality research in general and "safe sex" practices in particular. Most research models have been somewhat mechanistic in focus, however, with little recognition of the significance of affectional needs in the formation and maintenance of sexual relationships. In this paper we propose that relationship issues are central to an understanding of the expression of sexuality, and that attachment theory provides a useful per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
22
1
1
Order By: Relevance
“…Furthermore, an alternative model in which romantic attachment predicted parent-child relationship quality fit the data less well. These results support the argument that attachment theory can be used to understand LGB romantic pair bonds (Feeney & Raphael, 1992;Mohr, 2008).…”
supporting
confidence: 81%
“…Furthermore, an alternative model in which romantic attachment predicted parent-child relationship quality fit the data less well. These results support the argument that attachment theory can be used to understand LGB romantic pair bonds (Feeney & Raphael, 1992;Mohr, 2008).…”
supporting
confidence: 81%
“…Researchers (e.g., Feeney & Raphael, 1992) Results from our third study also highlight the applied value in finding novel ways to frame condom use in promotion messages. Framing condom use as a prosocial other-oriented act (Mikulincer et al, 2005) eliminated the decreases in condom acquisition that resulted from attachment security priming in the control condition and the other studies.…”
Section: Basic and Applied Implicationsmentioning
confidence: 57%
“…Meta-analyses of condom behavior studies revealed a central determining role for attitudes; if people hold a negative attitude about condoms they are unlikely to use them (Albaracín et al, 2005;Albaracín, Johnson, Fishbein, & Muellerleile, 2001;Sheeran, Abraham, & Orbell, 1999). A major limitation of the literature on condom-related attitudes, however, is its disregard of relational processes that influence condom use (Ciesla, Roberts, & Hewitt, 2004;Feeney & Raphael, 1992;WHO, 2012). Focusing on relational processes can help explain the motivational and emotion-based aspects of sexuality and condom use (Feeney & Raphael, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on HIV and attachment are mostly focused on attachment styles of adults with HIV (Feeney & Raphael, 1992;Koopman et al, 2000) or the attachment relationships of HIV-positive children (Dobrova-krol, Bakermans-Kranenburg, Van IJzendoorn, & Juffer, 2010). Only one study could be found on mother-infant attachment relationships where the mothers were HIV positive.…”
Section: Introductionmentioning
confidence: 99%